Different co-sensitizations could determine different risk assessment in peach allergy? Evaluation of an anaphylactic biomarker in Pru p 3 positive patients. Issue 1 (December 2015) - Uasuf, Carina; Villalta, Danilo; Conte, Maria; Sano, Caterina; Barrale, Maria; Cantisano, Vincenzo; Pace, Elisabetta; Gjomarkaj, Mark; Gangemi, Sebastiano; Brusca, Ignazio
Abstract Background In Italy, the nsLTP (Pru p 3) has been identified as the most frequent cause of food allergy and anaphylaxis. In order to estimate the risk assessment in peach allergy, we investigated the presence of correlations between the levels of sIgE to Pru p 3 with the severity of the clinical symptoms in two Pru p 3 positive populations from two different areas of Italy. Methods 133 consecutively Pru p 3 positive patients were recruited from South Italy, where the prevalence of PR-10 and profilin sensitization is low, and from North-East Italy, where the sensitization to pathogenesis related protein -10 (PR-10) and profilin is higher. Skin prick test (SPT) to peach extract and sIgE to peach panallergens were performed. Results All 133 patients were positive to SPT to peach extract and to sIgE to Pru p 3. The North-East population was simultaneously positive to Pru p 1 (42.8 %) and Pru p 4 (12.7 %), while no Southern patients were positive to PR-10 or to profilin. A significant difference in the levels of sIgE to Pru p 3 was found only in South Italy Pru p 3 + patients vs. asymptomatic patients (p = 0.01) and in mild reactions vs. severe reactions (p = 0.0008). In South Italy patients, it was also found a significant correlation between the severity of the clinical reaction and the levels of sIgE to Pru p 3 (p = 0.001). Conclusion Level of sIgE to Pru p 3 indicates the possibility of development a severe food allergic reaction. Pru p 3 positive patients from different geographical areas and with different co-sensitizations to Pru p 1 and/or Pru p 4 could have a different risk assessment in peach allergy.